Presentation of a branchial cleft anomaly in an adult. Issue 5 (May 2021) - Wojtas, Emily; Mendez, Anthony; Donald, Carrlene; Hinni, Michael
ABSTRACT: Branchial cleft anomalies are the second most common type of congenital neck mass and typically are diagnosed in patients under age 5 years. This article describes a rare presentation of an adult with a branchial cleft anomaly.